PERAN TUTOR DALAM MENANAMKAN NILAI KEDISIPLINAN PADA ANAK USIA DINI DI PKBM FINORIKEN OEPURA KOTA KUPANG - Hoar, Yuliarni; Kale, Sartika; Selly, Frans K (Universitas Nusa Cendana, 2023)
This study aims to: determine the of tutors in instilling early childhood discipline in PKBM finoriken kupang city, with a focus on research on the role of tutors as educators, mentors, and directors in instilling the value of discipline in early childhood at PKBM finoriken kupang city. This study uses descriptive qualitative methods conducted at PKBM finoriken oepura city kupang. The data collection techniques used in this research is interview, observation and documentation. The results showed that (1) the discipline of children at PKBM finoriken oepura, kupang city that before entering class, the tutor first checked student attendance through the attendance list, students had to be diligent in coming to school so that attendance was assessed to be guite increased, students got used to tidying up toys after when used, students must put their shoes on the shoe rack, students can throw garbage in its place and students must pay attention to the tutor during the learning process. (2) the role of the tutor in instilling the value of discipline in early childhood at PKBM finoriken oepura kupang city, which is in accordance with the approach method used in PKBM finoriken oepura kupang is the method of singing and playing games.